2019
DOI: 10.3390/md17080465
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Brominated Oxindole Alkaloids from the Red Sea Sponge Callyspongia siphonella

Abstract: In the present study, LC-HRESIMS-assisted dereplication along with bioactivity-guided isolation led to targeting two brominated oxindole alkaloids (compounds 1 and 2) which probably play a key role in the previously reported antibacterial, antibiofilm, and cytotoxicity of Callyspongia siphonella crude extracts. Both metabolites showed potent antibacterial activity against Gram-positive bacteria, Staphylococcus aureus (minimum inhibitory concentration (MIC) = 8 and 4 µg/mL) and Bacillus subtilis (MIC = 16 and 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 37 publications
1
49
0
Order By: Relevance
“…The antibacterial evaluation was performed for our small natural products library (Compounds 1-36, Table S1) in terms of MIC values in µM using standard antibacterial agents (ampicillin and gentamicin). The results of inhibitory evaluation along with our previous inhibitory reports on other bacterial strains [19] illustrated that a number of related indole derivatives were the only active compounds. The brominated oxindole derivatives, 5-bromotrisindoline and 6-bromotrisindoline (5-Tris and 6-Tris, respectively; Compounds 1 and 2; Table S1) were the most potent metabolites against Gram-positive bacterial MRSA (MIC 8 and 4 µM, respectively) and B. subtilis (MIC 4 and 4 µM/mL, respectively).…”
Section: Inhibitory Activity Screeningmentioning
confidence: 51%
See 2 more Smart Citations
“…The antibacterial evaluation was performed for our small natural products library (Compounds 1-36, Table S1) in terms of MIC values in µM using standard antibacterial agents (ampicillin and gentamicin). The results of inhibitory evaluation along with our previous inhibitory reports on other bacterial strains [19] illustrated that a number of related indole derivatives were the only active compounds. The brominated oxindole derivatives, 5-bromotrisindoline and 6-bromotrisindoline (5-Tris and 6-Tris, respectively; Compounds 1 and 2; Table S1) were the most potent metabolites against Gram-positive bacterial MRSA (MIC 8 and 4 µM, respectively) and B. subtilis (MIC 4 and 4 µM/mL, respectively).…”
Section: Inhibitory Activity Screeningmentioning
confidence: 51%
“…All compounds used in the present study (Compounds 1-36, Table S1, Supplementary Materials) were isolated from the Red Sea-derived sponge Callyspongia siphonella and its associated microorganisms using multiple chromatographic purification steps and using preparative HPLC (Agilent ® 1260 Infinity, CA, USA) as a final step to obtain these compounds in pure form. The detailed procedure of compounds extraction and isolation were described previously [17][18][19]. All chemical structures of the isolated natural metabolites were determined by analysis of their spectral data (MS and NMR) and comparison with reported literature.…”
Section: Library Constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intermediate isatin was detected during the biosynthesis of compounds 21 and 22. [23] Two novel double indoles alkaloids 23 and 24 were accessed from marine sponge Lamellomorpha strongylata containing the unusual α-ketovinylamide functionality. [12] Compounds 25 and 26 were firstly isolated from the sponge Spongosorites calcicola.…”
Section: Indole Alkaloidsmentioning
confidence: 99%
“…The results of Western blotting with IL8 (interleukin 8) assay suggested that non-programmed cell line necrosis triggered to the cytotoxicity by compound 21. [23] γ-Carboline alkaloid 27 displayed strong potency on the L5178Y (murine lymphoma) cell line with ED 50 values of 9.1 μg/mL compared to the positive control kahalalide F (ED 50 = 6.3 μg/mL). Another known compound with β-carboline possessed more potent activity, which meant that the β-carboline played a significant role in cytotoxic towards L5178Y.…”
Section: Cytotoxicitymentioning
confidence: 99%